Perencanaan Masa Depan Anak Melalui Kesadaran Karier Sejak Dini - Peni Okto Randi; Rizka Ahmad (Medan State University, 2021)
The purpose of writing this article is to provide an overview of the importance of career awareness in elementary schools. Starting with the theoretical framework, reasons are given for early intervention by the primary school counselor. Research that describes the practice of counseling in elementary schools is still minimal. The need for empirical practice will support the implementation of an integrated BK program on the theme of elementary school learning